Comparison Among Proton Pump Inhibitor Inducing Pneumonia in Hospital: Narrative Review - Sari, Juwita Permata; Nugroho, Agung Endro; Widyati, Widyati (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Critically ill patients requiring intensive care unit (ICU) are highly vulnerable to the emergence of stress-related gastrointestinal bleeding, a condition closely associated with unfavorable clinical outcomes. Despite advancements in preventive measures, antimicrobial therapies, and supportive medical care, ventilator-associated pneumonia (VAP) and hospital-acquired pneumonia (HAP) continue to effect morbidity and mortality rates significantly. Hospital-acquired pneumonia (HAP) is characterized as a form of pneumonia that does not manifest during the period of hospital admission but rather emerges 48 hours or later after the patient has been admitted. In contrast, VAP occurs after 48 hours of having an endotracheal tube in place. Proton pump inhibitors (PPIs) are used prophylactically to manage stress ulcers in critically ill patients. However, recent scholarly literature has drawn attention to a potential link between using acid-suppressing medications and an increased susceptibility to pneumonia. The precise mechanism through which these acid suppressors might elevate the risk of pneumonia remains unclear. The primary objective of this study was to assess the prevalence of pneumonia associated with different types of proton pump inhibitors. We conducted an extensive literature search using keywords such as